Population structure of the Chagas disease vector, Triatoma infestans, at the urban–rural interface. Issue 20 (19th September 2013) - Foley, Erica A.; Khatchikian, Camilo E.; Hwang, Josephine; Ancca‐Juárez, Jenny; Borrini‐Mayori, Katty; Quıspe‐Machaca, Victor R.; Levy, Michael Z.; Brisson, Dustin; ,
Abstract The increasing rate of biological invasions resulting from human transport or human‐mediated changes to the environment has had devastating ecological and public health consequences. The kissing bug, Triatoma infestans, has dispersed through the Peruvian city of Arequipa. The biological invasion of this insect has resulted in a public health crisis, putting thousands of residents of this city at risk of infection by Trypanosoma cruzi and subsequent development of Chagas disease. Here, we show that populations of Tria. infestans in geographically distinct districts within and around this urban centre share a common recent evolutionary history although current gene flow is restricted even between proximal sites. The population structure among the Tria. infestans in different districts is not correlated with the geographical distance between districts. These data suggest that migration among the districts is mediated by factors beyond the short‐range migratory capabilities of Tria. infestans and that human movement has played a significant role in the structuring of the Tria. infestans population in the region. Rapid urbanization across southern South America will continue to create suitable environments for Tria. infestans, and knowledge of its urban dispersal patterns may play a fundamental role in mitigating human disease risk.